2019
DOI: 10.5539/jel.v8n3p95
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the “Attitudes Toward Physical Activity Scale” for Higher Education Students in Turkey

Abstract: The purpose of this study was to adapt the "Attitudes toward Physical Activity Scale" (APAS) for Turkish higher education students. Study was conducted during 2018-2019 autumn semester at a public university in the central Anatolia region of Turkey. The APAS was applied to 1021 voluntary university students from eleven different faculties and departments of the university. Descriptive statistics, exploratory and confirmatory factor analyses, internal consistency coefficients were used in statistical analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…This study is the first conducted in Southeast Asia among Singaporean students. The findings from this study are similar to the findings from previous studies investigating the impact of Brain Breaks ® videos on students aged 9 to 11 years old in China [25], Malaysia [16], Turkey [31], Lithuania [33], Poland [28] and Macedonia [32], students 12 years old [36], and students in higher education [31]. These previous studies found that students utilizing Brain Breaks ® videos had positive changes in their attitudes towards PA.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This study is the first conducted in Southeast Asia among Singaporean students. The findings from this study are similar to the findings from previous studies investigating the impact of Brain Breaks ® videos on students aged 9 to 11 years old in China [25], Malaysia [16], Turkey [31], Lithuania [33], Poland [28] and Macedonia [32], students 12 years old [36], and students in higher education [31]. These previous studies found that students utilizing Brain Breaks ® videos had positive changes in their attitudes towards PA.…”
Section: Discussionsupporting
confidence: 88%
“…The seven scales in the original version of this questionnaire were validated for their reliabilities, uni-dimensionality, effectiveness of the response categories, and absence of gender differential item functioning (DIF) by Mok et al [30] using the Rasch analysis. A subsequent study by Dinc et al [31] updated the questionnaire and further enhanced internal consistency. The current study reported here made use of the updated version of APAS.…”
Section: Measures Students' Attitudes Toward Physical Activity Scale (Apas)mentioning
confidence: 99%
See 1 more Smart Citation